WHO ARE THE BREADWINNERS? Status, Rights and Responsibilities in Unregistered Polygamous Marriage in Indonesia - Wirastri, Theresia Dyah; van Huis, Stijn Cornelis (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2022)
Polygamy is a highly controversial topic and the object of serious political contestation in Indonesia. Although all major Muslim organizations consider polygamy is allowed under Islamic Law, the practice is not without stigma. In 1974 when Indonesia adopted its current Marriage Law, the Indonesian parliament decided to tie polygamy to strict conditions. This law however failed to prevent the practice of unregistered polygamous marriages. Women in unregistered polygamous marriages formally hold no rights as lawful wife in case of a divorce or death of the husband. The question is what arrangements the second, third or fourth wife in unregistered polygamous marriages have made with their husband in view of the lack of legal recognition of their rights as wife. What are the consequences of non-recognition of their marriage for these women? Does legal insecurity in practice also mean economic and social insecurity? Does the husband fulfill his obligations and responsibilities towards his wives and their families? This article aims at answering those questions by looking in-depth at a selection of three case studies, which were collected during a total of nine months of research in Jakarta in 2015 and 2016. This article is part of the socio-legal domain, combining legal analysis with anthropological approaches. The starting point of the research is a legal one: the disadvantaged legal position of women whose polygamous marriage has not been registered, but a large part of the research is based on anthropological methods. Through the experiences of these women, the paper reveals a range of personal reasons and underlying causes for unregistered Islamic polygamous marriages as well as their consequences–including legal ones. The paper depicts a great diversity in the ways husbands and wives view and organize their responsibilities within their polygamous households.